(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
The power can be generated using non-conventional energy sources. However, these sources are intermittent and unpredictable. Thus, the consumer power supply is not continuous. However, the combination of two or more non-conventional resources can make the supply continuous. The research proposal presented in this work explores an integrated non-isolated DC-DC power converter structure that has the parallel combination of traditional SEPIC (single-ended primary inductor converter) and voltage-gain-boosted Cuk configurations. The features of the proposed DC-DC power conversion structure include nonzero current flow through inductors, a reduced number of inductors and capacitors in the topology, reduced voltage stress on semiconductor-based components, and a relatively high step-up voltage gain. The operating modes of the topology are explored along with the derivation of the static voltage gain. To validate the effectiveness of the proposed integrated converter structure, an experimental setup is developed, and its results are compared with those of the MATLAB/Simulink model of the topology.